Hypofractionated Radiation Therapy for Large Brain Metastases - Masucci, Giuseppina Laura (Frontiers in Oncology, 2018)
Single fraction radiosurgery (SRS) treatment is an effective and recognized alternative to whole brain radiation for brain metastasis. However, SRS is not always possible, especially in tumours of a larger diameter where the administration of high dose in a single fraction is limited by the possibility of acute and late side effects and the dose to the surrounding organs at risk. Hypofractionated radiation therapy allows the delivery of high doses of radiation per fraction while minimizing adverse events, all the while maintaining good local control of lesions. The optimal dose fractionation has however not been established. This overwiew presents available evidence and rationale supporting usage of hypofractionated radiation therapy in the treatment of large brain metastases.